1984
DOI: 10.1016/0014-5793(84)80758-9
|View full text |Cite
|
Sign up to set email alerts
|

GTP interacts with the γ‐subunit of eukaryotic initiation factor eIF‐2

Abstract: Eukaryotic initiation factor eIF-2 is an oligorneric protein consisting of three different subunits. During initiation of protein synthesis eIF-2 interacts with GTP, Met-tRNAland 40 S ribosomal subunit. By afftnity labeling with a photo-reactive GTP analogue it was shown that in the binary complex [eIF-2. GTP] GTP is in contact with the y-subunit of eIF-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…subunit, are as active as complete eIF-2 in Met-tRNA, binding to 40s ribosomal subunits [38-421. (c) Because of its basic nature [18] the y subunit is the main candidate to contribute to the binding strength of the factor to the 40s subunit, and it seems to be logical that GTP was found to interact with the y subunit [16], if one considers that GTP hydrolysis is necessary for the release of eIF-2 from the 40s subunit (reviewed in [4,51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…subunit, are as active as complete eIF-2 in Met-tRNA, binding to 40s ribosomal subunits [38-421. (c) Because of its basic nature [18] the y subunit is the main candidate to contribute to the binding strength of the factor to the 40s subunit, and it seems to be logical that GTP was found to interact with the y subunit [16], if one considers that GTP hydrolysis is necessary for the release of eIF-2 from the 40s subunit (reviewed in [4,51).…”
Section: Discussionmentioning
confidence: 99%
“…Initiation factor eIF-2 was prepared from rat liver according to Nygard et al [15] with slight modifications briefly described by Kurzchalia et al [16]. The whole procedure was performed at about 2°C and in the presence of 0.2 mM phenylmethylsulfonyl fluoride to prevent proteolytic degradation.…”
Section: Preparation Of Initiation Factor Eif-2 and Of Its Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The gamma subunit of eIF2 is thought to bind both the initiator tRNA and the guanine nucleotide. 21,36,37 The structures of the wild-type protein in the absence of guanine nucleotide and the presence of GDP were determined, as were structures of a mutant form of the protein, G235D (thought to be in or near the MettRNA i binding site), in the absence of ligand and the presence of both GDP and GDPNP. The archaeal gamma subunit bears striking sequence and structural similarities to elongation factor EFTu/eEF1A.…”
Section: Structural Insightsmentioning
confidence: 99%
“…Surprisingly, there are still significant gaps in our knowledge ofeven the most basic mechanisms involved in the formation of the ternary complex. It was originally suggested that the GTP ligand binds to the ac subunit and Met-tRNAf to the , subunit [19], but more recent work using affinity labelling with photo-reactive analogues of GTP has indicated that guanine nucleotides bind either to the y [20] or the , (W. C. Merrick, personal communication) subunits. In the latter study the analytical system used was capable of distinguishing unambiguously between the and y subunits, and both studies included controls demonstrating specificity of association.…”
Section: Mechanism Of Initiation Of Translation In Mammalian Cellsmentioning
confidence: 99%